2012
DOI: 10.1248/bpb.b12-00378
|View full text |Cite
|
Sign up to set email alerts
|

New Cancer Immunotherapy Using Autologous Lymphocytes Activated with Trastuzumab

Abstract: It is well known that trastuzumab (TTZ) is molecular target drug for breast cancer overexpressing human epidermal growth factor receptor 2 (HER2). Novel immunotherapy by human peripheral blood mononuclear cells (PBMCs) activated with TTZ were examined. Proliferation of lymphocytes after adding of TTZ was obtained. Furthermore, lymphocytes activated with TTZ inhibited growth of breast cancer cells in vitro. It is noteworthy that remarkably high cellular cytotoxicity in lymphocytes activated with TTZ compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Manipulations of the Fc domain structure may optimize antibody clearance and the interaction of Fc domains with cellular Fc receptors (23). Furthermore, immobilization of TTZ increased the number of PBMCs from 5 healthy donors after 48 h of culture, which indicated that this technique is effective for culturing cells for immunotherapy (24).…”
Section: Large Scale Ex Vivo Expansion Of Clinical-grade Effector Celmentioning
confidence: 99%
“…Manipulations of the Fc domain structure may optimize antibody clearance and the interaction of Fc domains with cellular Fc receptors (23). Furthermore, immobilization of TTZ increased the number of PBMCs from 5 healthy donors after 48 h of culture, which indicated that this technique is effective for culturing cells for immunotherapy (24).…”
Section: Large Scale Ex Vivo Expansion Of Clinical-grade Effector Celmentioning
confidence: 99%
“…22) Activation of the lymphocytes having Fc receptor (FcR) in TTZ-LAK cells could enhance cellular cytotoxicity. On the other hand, T cells which recognized a specific antigen (HER2) produced by human breast cancer cells in TTZ-LAK cells could also induce cytotoxic T-lymphocyte (CTL) by antigen presentation to lymphocyte.…”
Section: Therapeutic Effects Of Ttz-lak For Xenograft Mouse Models Ofmentioning
confidence: 99%
“…We have already reported on inhibitory effects of lymphocytes activated with TTZ (TTZ-LAK) on the growth of human breast cancer cells in vitro. 22) However, anticancer effects of TTZ-LAK in vivo have not been elucidated.…”
mentioning
confidence: 99%
“…Therefore, how to treat LCSC must be considered after an operation, radiotherapy and/or chemotherapy. Autoimmune treatment of a malignant tumor is considered to be a feasible method, that mainly depends on the interfering and suppressing effects of killer cells induced by the tumor, infiltrating lymphocytes and lymphokines, as well as CD3 monoclonal antibodies [ 8 , 9 ]. Currently, cytokine-induced killer cells (CIK) therapy or dendritic cells (DC)-CIK cell co-cultivation has been widely used to treat malignant tumors in clinical trials, because DC and CIK have been demonstrated to possess high antitumor and cytotoxic activity against hepatocellular carcinoma (HCC) cells in vitro and in vivo [ 10 12 ].…”
Section: Introductionmentioning
confidence: 99%